Computational insights into electronic characteristics of 2D PtSe2 nanomaterials: Effects of vacancy defects and strain engineering. (December 2021) - Liu, Guogang; Chen, Tong; Xu, Zhonghui; Zhou, Guanghui; Xiao, Xianbo
Abstract: The epitaxial growth of PtSe2 monolayer has brings new opportunities for the application and development of materials science. Using first-principles calculations, the effect of vacancy defects, and strain engineering on the electronic properties of PtSe2 monolayer are systematically investigated. The results show that the Pt single vacancy induces a large magnetic moment of 4.0 μ B on PtSe2 monolayer and transforms it from semiconductor to metal. However, the Se single vacancy systems are nonmagnetic and realize the PtSe2 from an indirect semiconductor to a direct one. Moreover, the band gap of PtSe2 monolayer can be prominently modulated within a appreciable uniaxial strain range, and the band gap are monotonically increase/decrease as decrease/increase the magnitude of the compressive/tensile strain. In particular, when a specific strain applied, a wide and high absorption peak across near-infrared, visible light and ultraviolet region. These findings not only enrich the fundamental understanding of PtSe2 monolayer but also provide useful guidance to design PtSe2 -based spintronic, optoelectronic and gas sensing applications. Highlights: Pt single vacancy induces a large magnetic moment and transforms PtSe2 from semiconductor to metal. The band gaps of 2D PtSe2 are monotonically increase/decreas as decrease/increase the magnitude of the compressive/tensile strain. Applying external strain reduce the band gap of PtSe2 monolayer.